Patient Satisfaction Level and Vision-Related Quality of Life: A Comparison between Trifocal and Diffractive Extended Depth of Focus (EDOF) IOLs - Latif, Ejaz; Ijaz, Mehlab; Ali, Haseeb; Ejaz, Aqsa; Mehboob Ali Bana, Kiran Fatima; Chaudhary, Farah (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To compare patient satisfaction level and vision-related quality of life after Trifocal and EDOF implants to treat cataracts among the population of Southern Punjab. METHODOLOGY: This comparative practice-based study was conducted at the Sight Centre of Bahawalpur City of Southern Punjab from August 2022 to July 2023. Informed consent was obtained from all the subjects. A total of n=120 eyes were operated in two EDOF and Trifocal treatment cohorts. VR-QOL was assessed for near, intermediate, and distant vision. The data was analyzed on SPSS version 27. The p-value < 0.05 was considered statistically significant. RESULTS: There were n=29 (48.3%) males and n=31 (51.6%) females. The majority n=21 (35%) of subjects were aged 40-49. It was revealed that trifocal IOL demonstrated improved mean rank for near and intermediate vision. Statistically, a significant difference was found between putting thread into the needle and the mobile phone's utility at p-values of 0.047 and 0.040, respectively. Trifocal IOLs frequently generated the halo photic effect for light scattering at a P-value of 0.0001. Significant improvement was revealed in the VA of both eyes. The vision improved (100%) with Trifocal and EDOF group treatment options. Both treatment cohorts were satisfied with the final surgical outcome. CONCLUSION: VA was improved after implanting Trifocal and EDOF IOLs. Trifocal IOL demonstrated better performance at near & distant vision. The halo photic effect was generated more frequently by the trifocal IOLs. Patients were equally satisfied with the surgical outcome of both treatment options.